Association of MYCN copy number with clinical features, tumor biology, and outcomes in neuroblastoma: A report from the Children's Oncology Group. Issue 21 (11th July 2017) - Campbell, Kevin; Gastier‐Foster, Julie M.; Mann, Meegan; Naranjo, Arlene H.; Van Ryn, Collin; Bagatell, Rochelle; Matthay, Katherine K.; London, Wendy B.; Irwin, Meredith S.; Shimada, Hiroyuki; Granger, M. Meaghan; Hogarty, Michael D.; et al.
Abstract : BACKGROUND: High‐level MYCN amplification (MNA) is associated with poor outcome and unfavorable clinical and biological features in patients with neuroblastoma. To the authors' knowledge, less is known regarding these associations in patients with low‐level MYCN copy number increases. METHODS: In this retrospective study, the authors classified patients has having tumors with MYCN wild‐type tumors, MYCN gain (2‐4‐fold increase in MYCN signal compared with the reference probe), or MNA (>4‐fold increase). Tests of trend were used to investigate ordered associations between MYCN copy number category and features of interest. Log‐rank tests and Cox models compared event‐free survival and overall survival by subgroup. RESULTS: Among 4672 patients, 3694 (79.1%) had MYCN wild‐type tumors, 133 (2.8%) had MYCN gain, and 845 (18.1%) had MNA. For each clinical/biological feature, the percentage of patients with an unfavorable feature was lowest in the MYCN wild‐type category, intermediate in the MYCN gain category, and highest in the MNA category ( P <.0001), except for 11q aberration, for which the highest rates were in the MYCN gain category. Patients with MYCN gain had inferior event‐free survival and overall survival compared with those with MYCN wild‐type. Among patients with high‐risk disease, MYCN gain was associated with the lowest response rate after chemotherapy. Patients with non‐stage 4 disease (according to the International Neuroblastoma Staging System) and patients with non‐high‐risk disease with MYCN gain had a significantly increased risk for death, a finding confirmed on multivariable testing. CONCLUSIONS: Increasing MYCN copy number is associated with an increasingly higher rate of unfavorable clinical/biological features, with 11q aberration being an exception. Patients with MYCN gain appear to have inferior outcomes, especially in otherwise more favorable groups. Cancer 2017;123:4224–4235. © 2017 American Cancer Society . Abstract : MYCN amplification is an established adverse prognostic factor in patients with neuroblastoma, although to the authors' knowledge little is known regarding patients with tumors with low‐level copy number gain. Herein, the authors evaluate associations between MYCN copy number category and clinical features, biological features, and prognosis.